Breastfeeding in Focus: Causes of Early Weaning and the Obstacles to Overcome - Kist, Alessandra Maisa (2025)
Breastfeeding is an essential process for the nutrition and development of babies. Despite the recommendacions of the   World Health Organization (WHO) and the Ministry of Health, which indicate exclusive breastfeeding until six month of life, many babies end up being weaned early. To identify the main causes that lead to early weaning in a municipality in the interior of Paraná. This study was haracterized as a cross-sectional, descriptive and exploratory research, with a quantitative-qualitative approach, aimed at woen who stopped breastfeeding before six months of age. The main problems highlighted by the participants were the difficulty in breastfeeding and the lack of information during pregnancy. The present study identified the main causes of early weaning and the challenges faced by mothers during the breastfeeding process, emphasizing the importance of professional health support. The lack of adequate information and practical difficulties in breastfeeding were highlighted as factors that contribute to the early interruption of breastfeeding.